2017
DOI: 10.1063/1.4974779
|View full text |Cite
|
Sign up to set email alerts
|

Shaped cathodes for the production of ultra-short multi-electron pulses

Abstract: An electrostatic electron source design capable of producing sub-20 femtoseconds (rms) multi-electron pulses is presented. The photoelectron gun concept builds upon geometrical electric field enhancement at the cathode surface. Particle tracer simulations indicate the generation of extremely short bunches even beyond 40 cm of propagation. Comparisons with compact electron sources commonly used for femtosecond electron diffraction are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…As the cathode radius of curvature gets smaller and becomes comparable to the laser spot size, both transverse and longitudinal effects need to be considered. The electric field enhancement along a curved surface discussed earlier, can be used to increase the accelerating field in the cathode area while keeping a large transverse emission size, obtaining at the same time extraction of multi-electron beams and ultrashort pulses from setups with otherwise modest accelerating gradients, typically DC guns (Petruk et al, 2017). A similar approach can be taken in cathodes for RF guns.…”
Section: The Effect Of the Cathode Curvaturementioning
confidence: 99%
“…As the cathode radius of curvature gets smaller and becomes comparable to the laser spot size, both transverse and longitudinal effects need to be considered. The electric field enhancement along a curved surface discussed earlier, can be used to increase the accelerating field in the cathode area while keeping a large transverse emission size, obtaining at the same time extraction of multi-electron beams and ultrashort pulses from setups with otherwise modest accelerating gradients, typically DC guns (Petruk et al, 2017). A similar approach can be taken in cathodes for RF guns.…”
Section: The Effect Of the Cathode Curvaturementioning
confidence: 99%
“…Hence, a more general expression for Equation (16) follows, Equation 17: In all aforementioned FED experiments, the temporal resolution was in the range of ≈ 100 -350-fs. In pursuit of a different DC fs-electron gun concept capable of producing sub-100-fs, and ideally sub-30-fs multi-electron bunches, Petruk et al [224] found that ∆t p is governed the strength of the electric field at the cathode's surface since most of the temporal broadening occurs during the initial stage of electron propagation [225]. Hence, a more general expression for Equation (16) follows, Equation 17:…”
Section: Bright Compact Direct Current (Dc) Fed Setupsmentioning
confidence: 99%
“…where E g is the magnitude of the geometrical electric field at the cathode's surface, i.e., in the area where electrons are born.] Equation (17) stresses the need to achieve both high electric field strengths and low initial momentum (or energy) spread at the cathode's surface in order to minimize the temporal broadening caused by ∆p 0 as well as additional broadening arising from instabilities in the high-voltage power supply [224]. Note that ∆p 0 affects both the temporal and spatial resolutions (see definition of L x in Equation (6)).…”
Section: Bright Compact Direct Current (Dc) Fed Setupsmentioning
confidence: 99%
“…By increasing the energy of short pulses of electrons to the megaelectron volt regime, the space charge effect can be suppressed, which has enabled electron pulses of tens of picocoulombs and hundreds of femtoseconds as well as sub-10-fs electron pulses of tens of femtocoulombs [21][22][23] . A technique has also been developed for minimizing the influence of the space charge effect by placing the specimen or measurement position very close to the DC electron gun 24,25 . Although this method can suppress the increase of electron energy, the space charge effect remains as a limitation.…”
mentioning
confidence: 99%